2020
DOI: 10.2174/1871530319666191008170409
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Metabolic Syndrome and Psoriasis: A Systematic Review and Meta-Analysis of Observational Study

Abstract: Background: Metabolic syndrome worsens complications in psoriasis patients by predisposing them to cardiovascular diseases. Psoriasis has been widely associated with metabolic syndrome; however, it has still not been proven owing to a limited number of studies and some of those reporting conflicting results. Objective: Psoriasis has reportedly been associated with metabolic syndrome; however, it has yet not been established beyond doubt owing to conflicting literature. The present meta-analysis of observatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 83 publications
3
29
0
2
Order By: Relevance
“…A recent meta-analysis (63 studies encompassing 15,939 psoriasis patients and 103,984 controls) showed that 30.3% of psoriasis patients were reported with MetS compared with 21.7% subjects in the control group [OR 2.18 (95% CI 1.84-2.34)] [22]. Similarly, another meta-analysis showed that the association between psoriasis and MetS is high in Latin America [23].…”
Section: Obesity and Metsmentioning
confidence: 99%
“…A recent meta-analysis (63 studies encompassing 15,939 psoriasis patients and 103,984 controls) showed that 30.3% of psoriasis patients were reported with MetS compared with 21.7% subjects in the control group [OR 2.18 (95% CI 1.84-2.34)] [22]. Similarly, another meta-analysis showed that the association between psoriasis and MetS is high in Latin America [23].…”
Section: Obesity and Metsmentioning
confidence: 99%
“…By the end of the followup period (median of just over 5 years), the hypertension prevalence rose to 24.72% (mild psoriasis) and 31.62% (severe psoriasis), and 31.6% among controls. 5 Other studies found outcomes in similar prevalence ranges of 30%, 18 32.8%, 19 32%, 17 34.3%, 10 and 35%, 13 respectively. In the Brigham study the prevalence was reports at 45%.…”
Section: Hypertensionmentioning
confidence: 88%
“…Psoriasis increases the incidence of these diseases and is considered to represent an aggravating factor by itself. A systematic review of the risk of CVD risk factors in psoriasis and recent findings from a meta‐analysis are summarized in Table 1 20,44‐54 …”
Section: Psoriasis and Cvdmentioning
confidence: 99%